Study on Traditional Learning & E-Learning and its impact on Academic Achievements of Secondary Level Student: A Comparative Study on the Efficiency of Traditional and E-Learning for Secondary School Students (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Introduction One solution to the difficulty posed by globalization, technological advancements, and demographicshifts is the availability of opportunities for lifelong education. All facets of society are now ruled by technology.Aim of the study the main aim of the study is to Traditional Learning E-Learning And Its Impact On AcademicAchievements Of Secondary Level StudentMaterial and method A Research Design, as defined by Claire Selltiz et al. (1991), compiles all of theinformation and steps necessary to create a study.Conclusion This research set intended to compare the efficiency of online education to more conventionalmeans of instruction for secondary school pupils. E-learning has been shown to be more efficient thanconventional teaching approaches.